Improvement on mechanical properties and study of manufacturability of printed part fabricated via open source 3D printer - Mazlan, Siti Nur Humaira (UTeM, 2018)
3D printing or also known as additive manufacturing (AM) has been introduced to fabricate the prototypes in shorter time and cost-effective. AM also capable to fabricate complex part geometry without any additional tooling and jigs required. One of the most well-known techniques in AM is fused deposition modeling (FDM). However, the main bottleneck of FDM is its design manufacturabillity and printed part quality in terms of surface roughness, tensile strength and dimensional accuracy. In this research, the 3D printing processing methods using FDM were discussed to study the effect of pre-process, in-process and post-processing technique on mechanical properties and manufacturability of open source 3D printed parts. As for pre-processing, Taguchi analysis was conducted to find the optimum printing parameter settings. Meanwhile, for in-processing method, inert gas assisted 3D printing was evaluated. Then, the post-processing method which involves improvement of fully completed printed part was analyzed. The laser post-treatment and blow cold acetone vapor is used for post-processing method. Based on the comparison made, inert gas assisted 3D printing technique was selected as the best improvement method because of its capability to improve the overall part’s quality including surface roughness, tensile strength and dimensional accuracy. In order to identify the design limitation for FDM, the manufacturability and design attributes were studied. The manufacturability study involves some of the difference features of overhang, bridges, wall thickness, small hole diameter and wire diameter. Based on the information, test model 1, 2 and 3 was fabricated using inert gas assisted 3D printer machine. The dimensional accuracy for the test model was compared to original 3D printing technique. In general, it was found that, the 3D printed part’s surface roughness was improved by 45% for inert gas assisted method, 63% for laser post-treatment and 94% for blow cold acetone vapor. For tensile strength, 36% improvement made using inert gas assisted method, while for the other post-processing method, the tensile strength is significantly reduces. The dimensional accuracy was also improved for the test model structure up to 39% improvement when using inert gas assisted method. The study has successfully identified the design limitation, and developed design guideline for open source 3D printer. The information can be useful to all 3D printer users to avoid the laborious and time consuming trials during manufacturing process of the prototype.